The oral communicative strategies of university engineering students in the South-Western Nigeria - Abdullateef Solihu, Abdullateef; Mohamad Isa, Abdul Azim; Mohd Noor, Maizura (Universiti Teknologi MARA, 2025)
This study was an attempt to explore the oral communicative strategies employed by a group of South-Western Nigerian undergraduate engineering students to navigate communication breakdowns during English interactions. A survey adapted from Alahmed (2017) was administered to a sample of 316 respondents across five public universities in South-Western Nigeria. Using The descriptive analysis reveal that the participants use a variety of oral communicative strategies (ranging from avoidance, paraphrase, conscious transfer, appeal for assistance and mime, stalling mechanisms, self-repair devices and meaning negotiation strategies). Mime and negotiation for meaning were frequently used, while word coinage was least employed. Further research is recommended to generalize findings to a broader Nigerian ESL learner population. This study aims to inform pedagogical practices for university-level engineering students, language education policymakers, and language instructors on integrating communication strategies to enhance communicative competence.